Numerical computation of spin-transfer torques for antiferromagnetic domain walls - Park, Hyeon-Jong; Jeong, Yunboo; Oh, Se-Hyeok; Go, Gyungchoon; Oh, Jung Hyun; Kim, Kyoung-Whan; Lee, Hyun-Woo; Lee, Kyung-Jin (AMER PHYSICAL SOC, 2020)
We numerically compute current-induced spin-transfer torques for antiferromagnetic domain walls, based on a linear response theory in a tight-binding model. We find that, unlike for ferromagnetic domain-wall motion, the contribution of adiabatic spin torque to antiferromagnetic domain-wall motion is negligible, consistent with previous theories. As a result, the nonadiabatic spin-transfer torque is a main driving torque for antiferromagnetic domain-wall motion. Moreover, the nonadiabatic spin-transfer torque for narrower antiferromagnetic domain walls increases more rapidly than that for ferromagnetic domain walls, which is attributed to the enhanced spin mistracking process for antiferromagnetic domain walls.
Keywords: MOTION; DYNAMICS